Analysis of Gliding Sport Enthusiast - Humaid Junior, Ghazi Satriando; Aldianto, Leo; Ramania, Nia Sri; Putra, Narendra Kurnia (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
The purpose of this study is to figure out people who has an enthusiasm on gliding sport by looking on their geodemography and psychography, because gliding sport still uncommon for people in Indonesia. This study uses survey method with Google Form as an instrument. The subject of this study are 15 customers of Jakarta Soaring Club. The result of this study shows that mostly the customers of Jakarta Soaring Club come from a male in the age of 21 – 26 years old, have a bachelor’s degree, working as a company employee, have a monthly salary between RP 10.000.000 – 15.000.000, lives in Jabodetabek, and have an adrenaline junkie. The conclusion of this study is the gliding sport enthusiast come from upper-level society who have an interest in gliding and high adrenaline sport, so they choose gliding sport as an activity to do their hobby and interest. This research can conclude that gliding is still an exclusive sport in Indonesia due to expensive fee and difficult access. To expand this sport and for gaining more enthusiasts, we must promote this sport more often especially to those who matched the demography and psychography characteristics based on this survey. The discussion among gliding sport enthusiasts showcased a vibrant and passionate community dedicated to the unique experience of soaring through the skies. From technical details to the camaraderie and environmental considerations, participants demonstrated a holistic approach to gliding, emphasizing the need for continuous learning, safety, and community support within this exhilarating sport.Key words: Analysis, Gliding, Enthusiast, Sport